Structure and psychometrie verification of the personal independence questionnaire - Odej, Adam; Tokarski, Stanisław (Studia Psychologica: Theoria et praxis, 2009)
In the literaturę, we can find an enormous yariety of opinions concerning independency (self-dependency, self-reliance) and forms in which independency is expressed. They allow to create general view of independency and its specific symptoms. That forms a theoretical base of the questionnaire described here. After determining yariables: independency and upbringing to independency, they were given to the process of operationalization. The analysis of the items as well as the factor analysis were used to choose the final list of the questionnaire items. Psychometric characteristics of the Personal Independency Questionnaire were also yerified: reliability and precision were estimated in the group of 200 people. The reliability of Personal Independency Questionnaire was defined: Cronbach’s alpha coefficient half split and internal consistency were calculated. The factor analysis was used to define theoretical precision of the questionnaire and “test by test” method - to define its criterion precision.